Women and Collaborative Leadership: Promoting Strategic Roles in Local Social Dynamics - Suci Ramadhani; Ahmad Gautsul Anam; Aprilia Maulida; Martiana Martiana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This community service activity aims to develop female students' collaborative leadership within the context of local social dynamics through the Islamic and Gender School program organized by KOPRI PMII UIN Mataram. The method employed is a qualitative approach with interactive lectures, focused group discussions, and practical workshops involving 45 female students. The results demonstrate a significant increase in participants' understanding of collaborative leadership models based on Islamic values, with 87% of participants able to identify characteristics of collaborative leadership and 92% showing increased confidence in taking strategic roles in local communities. The discussion encompasses the concept of collaborative leadership in Islamic perspectives, strategies for building networks and partnerships, and women's leadership practices in addressing local social issues. This activity successfully encourages participants to develop leadership initiatives responsive to local community needs while strengthening women's strategic roles in social transformation. In conclusion, the collaborative leadership approach proves effective in empowering female students as agents of change in local social dynamics.